2016
DOI: 10.1007/s00128-016-1893-5
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Uptake by Muskmelon (Cucumis melo) Plants from Contaminated Water

Abstract: Arsenic is a carcinogenic element that occurs naturally in the environment. High levels of arsenic are found in water in some parts of the world, including Texas. The aims of this study were to determine the distribution of arsenic in muskmelon (Cucumis melo) plants accumulated from arsenic spiked water and to observe effects on plant biomass. Plants were grown and irrigated using water spiked with variable concentrations of arsenic. Inductively coupled plasma mass spectrometry was used to quantify arsenic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…These results coincide with those of other researchers, who showed that small As amounts stimulate plant growth (Gulz et al, 2005;Spagnoletti et al, 2015). As reported by Hettick et al (2016), when melon (Cucumis melo) was exposed to irrigation with 10 mg/L of As, it developed a greater biomass than the control. Carbonell-Barrachina et al (1995) observed that arsenate applications at 0.2e0.8 mg/L concentrations in hydroponic culture significantly increased root and stem dry matter yield of Spartina alterniflora and Spartina patens, as compared to control plants.…”
Section: Growth Of Chard Varieties When Exposed To Arsenicsupporting
confidence: 92%
“…These results coincide with those of other researchers, who showed that small As amounts stimulate plant growth (Gulz et al, 2005;Spagnoletti et al, 2015). As reported by Hettick et al (2016), when melon (Cucumis melo) was exposed to irrigation with 10 mg/L of As, it developed a greater biomass than the control. Carbonell-Barrachina et al (1995) observed that arsenate applications at 0.2e0.8 mg/L concentrations in hydroponic culture significantly increased root and stem dry matter yield of Spartina alterniflora and Spartina patens, as compared to control plants.…”
Section: Growth Of Chard Varieties When Exposed To Arsenicsupporting
confidence: 92%
“…This is because arsenic accumulates mainly in the root, while only a small portion is translocated to shoots with even smaller quantities to fruits [38]. Several studies have shown the presence of arsenic in fruits at very low concentrations [13,39,40], and so the risk for human consumption is very low.…”
Section: Discussionmentioning
confidence: 99%